2018
DOI: 10.3390/ph11030084
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Iron Metabolism in Response to Infection: Twists for All Tastes

Abstract: Iron is an essential nutrient for almost all living organisms, but is not easily made available. Hosts and pathogens engage in a fight for the metal during an infection, leading to major alterations in the host’s iron metabolism. Important pathological consequences can emerge from the mentioned interaction, including anemia. Several recent reports have highlighted the alterations in iron metabolism caused by different types of infection, and several possible therapeutic strategies emerge, based on the targetin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 149 publications
(176 reference statements)
0
34
0
4
Order By: Relevance
“…They recycle senescent red blood cells and nurse the formation of new ones [11][12][13] , thus participating in the major systemic iron fluxes occurring in higher vertebrates. Macrophages are also a first line of defence against pathogens, and they modulate iron availability as part of host protective mechanisms 12,[14][15][16] .…”
mentioning
confidence: 99%
“…They recycle senescent red blood cells and nurse the formation of new ones [11][12][13] , thus participating in the major systemic iron fluxes occurring in higher vertebrates. Macrophages are also a first line of defence against pathogens, and they modulate iron availability as part of host protective mechanisms 12,[14][15][16] .…”
mentioning
confidence: 99%
“…Another experimental study supporting this is by Ellison et al who proved that there is minimal transcriptional response after iron depletion in rickettsial culture exposed to iron chelator 24 hours after in vitro treatment [30]. Moreover, it is observed that Orientia tsutsugamushi infect human monocytic cells and increases expression of Interferon type-1 genes resulting in a M1 type of Monocyte-macrophage phenotype which sequesters iron within macrophages [31,32].…”
Section: Discussionmentioning
confidence: 84%
“…Given that pathogens fundamentally need iron to survive and proliferate, iron chelators have been suggested as a plausible strategy to treat infections, including mycobacteriosis [198]. We have previously shown that the addition of iron chelators to M. avium, in axenic cultures, in macrophage cultures, or in vivo, led to significant decreases in mycobacterial growth [199,200].…”
Section: Iron Chelatorsmentioning
confidence: 97%
“…Given the host's need for iron for their own metabolic needs, one important concern related to iron chelation therapies is the development of adequate cell-targeting strategies that may guarantee iron depletion in the pathogen without a concomitant deficiency in the host [198]. From the data available so far, chelators alone don't seem to exhibit a strong enough antimycobacterial activity, but they may have a role as an adjunct therapy, together with conventional antibiotics.…”
Section: Iron Chelatorsmentioning
confidence: 99%